Central banking in undeveloped money markets - Sen, S.N. (Calcutta, 1961)
The first edition of this book, written in the earlier half of 1951, contained an analysis of central banking legislation and practices in a number of countries with under-developed money markets upto the end of the year 1950. The last ten years have been very fruitful from this point of view: they have witnessed the spread of central banking to a large number of other countries, and have been remarkable for the evolution of newer techniques of central banking control. When, however, I was asked by the Publishers to prepare a new edition, I decided, after much consideration, to leave the general structure of the book as it was; providing a picture of some aspects of central banking in under-developed money markets in the first half of the twentieth century. The task of analysing the post 1950 developments should best be left to another work. So only a few changes have been made in this edition. Chapter 6 on the Australian System of Special Accounts has been rounded off with a brief description of its end in 1959. A new Chapter deals with the Indian experiment with Selective Credit Control upto the end of 1958. This was originally published in the Arthaniti, the journal of the Department of Economics of the Calcutta University. The appendix on Selective Control of Bank Lending was prepared for discussion in the Seminar of the Third SEANZA Central Banking Course held at Bombay in February, 1960. It was later published in the Journal of the Indian Institute of Bankers. In addition, some changes have been made in Chapters 1, 2 and 5.
Keywords: Banking